PERANCANGAN MEDIA INTERAKTIF SENI BELADIRI TARUNG DERAJAT - HABIB BERTA, Drs. Syafwandi, M.Sn, Ishakawi, S.Pd., M.Ds (DEKAVE : Jurnal Desain Komunikasi Visual, 2014)
Martial arts is the art that arises as the way a person maintain / defend themselves. Martial arts have long existed and evolved over time. Basically, humans have the instinct to always protect themselves and their lives. grow or evolve, human beings can not be separated from physical activity, whenever and wherever.In today's information age is a basic need of society. In the development of information technology is very easy to obtain. At the current state of fighting degrees should have a better media campaign or effective than previous media campaigns.Since fighting degrees established, fighting degrees yet have interactive media. Interactive media is the media campaign which aims to indirectly raise the degree of fighting image among the general public as well as the West Sumatran kususnya can introduce degrees Pasaman fighting in more detail.The design process will be applied to the CD or commonly called Interactive CD premises. The advantages of this CD is copied and does not require much cost. Therefore interactive media through a CD that is packaged very well to do a promotion for fighting degreesKeywords : fighting degrees, Promotion, Media Interaktif.